Fire alert system through text messages, with arduino mega technology and GSM SIM 900 module - Omar Chamorro Atalaya; Dora Arce Santillan (Institute of Advanced Engineering and Science, 2020)
The purpose of this article is to develop a fire alert system, to implement under the use of Arduino Mega technology and GSM module SIM 900 (GSM: Global System for mobile communications, SIM: Minimum System), with which through The programming and interconnection between these components can be obtained by capturing data through MQ2 sensors installed in the Industrial Automation Laboratory of the National Technological University of South Lima, and then send a fire alert signal through text messages to a mobile equipment located outside the laboratory; at a distance of 1000 meters; The relevance of this research is that its optimal response, detects the application of this system to the industrial park of Villa El Salvador, which has multiple warehouses, which a newspaper is affected by fire hazards, by the amount of flammable material They owned. Developing the investigation will determine the existence of a correlation factor of 0.973, between the reception time of the alert signal, with respect to the distance in the MQ2 sensor to detect the smoke; This factor tells us to state that the correlation is significant between both variables; with a ratio percentage equal to 98.90%, which was selected by the determination factor R2.